Distribution of canine distemper virus and nectin-4 in raccoon (Procyon lotor) skin. Issue 5 (September 2022) - Garcia, Pedro A. Triana; Cartoceti, Andrew; Affolter, Verena K.; Jackson, Kenneth; Keel, M. Kevin; Agnew, Dalen; Cooley, Thomas; Melotti, Julie; Fitzgerald, Scott D.; Pesavento, Patricia A.
Raccoons ( Procyon lotor ) are abundant in urban/wildland interfaces and are key sources of canine distemper virus (CDV) outbreaks in domestic, zoo, and free-ranging wildlife species. CDV is pantropic, which provides multiple potential routes of transmission (urine, respiratory secretions, feces), but the specific role of skin as a target of infection, as a diagnostic sample, or as a potential source of environmental persistence and transmission is unknown. We have characterized the distribution of CDV and its known receptor, nectin-4, in skin samples of 36 raccoons. Even with skin samples that were grossly and histologically normal, immunohistochemistry of skin was useful in the diagnosis of CDV infection, which was found in both epithelium and endothelium. Nectin-4 was codistributed with cellular targets of viral infection. Skin secretions, shed keratinocytes, and hair of CDV infected raccoons are all potential environmental fomites.